ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, AND CAPITAL (RGEC) PADA BANK UMUM SWASTA YANG TERCATAT DI BEI TAHUN 2019-2020 (Jurnal Akuntansi, 2023)
This study aims to determine the soundness of National Private Commercial Banks listed on the Indonesia Stock Exchange in 2019-2021 using the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) method in terms of NPL, LDR, GCG, ROA, NIM, and CAR. This type of research is quantitative research and the data sources used in this research are secondary data. The research population is all National Private Commercial Banks listed on the Indonesia Stock Exchange using purposive sampling technique to obtain four (4) National Private Commercial Banks as samples in this study. The results of this study indicate that the financial performance of BUSN banks during 2019-2021 seen from the Risk Profile is ranked 2 (PK-2) in the "healthy" category, Good Corporate Governance is ranked 2 (PK-2) in the "healthy" category, Earning is ranked 1 (PK-1) in the â€œvery healthyâ€ category, and Capital is ranked 1 (PK-1) in the â€œvery healthyâ€ category. In general, the Financial Performance of National Private Commercial Banks in 2019-2021 is included in the "Healthy" category with an average score of 82.66 percent. The implication of this research is as information that presents the level of soundness of National Private Commercial Banks listed on the Indonesia Stock Exchange.